Relationship between Work Climate and Physical Workload with Work-Related Fatigue - Mustofani Mustofani; Endang Dwiyanti (Universitas Airlangga, 2019)
Introduction: Work-related fatigue is a common problem in the workplace that must be solved because it has an impact on the occurrence of workplace accidents, reduces productivity and affects workers’ health. A survey conducted by the National Safety Council on 2010 workers in 2017 stated that 69% of them experienced work-related fatigue and 13% of them could be attributed to workplace accidents. Other studies conducted by O'Neill and Panuwatwanich in 2013 stated the loss that could arise due to work-related fatigue is averaged around 1,000/week. The purpose of this study was to determine the relationship between work climate and physical workload with work-related fatigue on workers in the 5th warehouse of fabrication area of Bangun Sarana Baja Company. Metods: This study is an observational analytic with a cross-sectional approach with 30 respondents who were randomly selected using the simple random sampling method. Measurements of the work climate used heat stress apparatus by calculating the Wet Bulb Globe Temperature, and measurement of physical workload is carried out by observations referring to Indonesian national standard No. 7269 in 2009. Meanwhile, work-related fatigue is measured objectively by using reaction timer. Results: This study indicates the average work climate is exceeding TLV (28.4° C), and the majority of workers got a moderate physical workload (53.3%) and experience mild work-related fatigue (50%). Conclusion: There was no relation between work climate and work-related fatigue (p-value = 0.192) and there was a significant relationship between physical workload and work-related fatigue (p-value = 0.028, r = 0.400). Keywords: physcal workload, work climate, work-related fatigue